I need a step by step explanation for this solution.

Community Answer

(i) given x(t)=t,quad0 < t < (T_(0))/(2)x(t)=t,quad0 <= t < (T)/(2)x((T_(0))/(2))=(T_(0))/(2)for half-wave symmetryx(t+(T_(0))/(2))=-x(t)=>x(t)=-x(t+(T_(0))/(2))at t=(T_(0))/(3)at t=(T_(0))/(3),x((T_(0))/(3))=(T_(0))/(3){:[x(t+(T_(0))/(2))=-x(t)],[t=(T_(0))/(3)quad x((T_(0))/(3)+(T_(0))/(2))=-x((T_(0))/(3))=>x((5T_(0))/(6))=-x((T_(0))/(3))]:}x(5(T_(0))/(6))=-(T_(0))/(3)". "{:[x((T_(0))/(2))=(T_(0))/(2)],[x((T_(0))/(2)+(T_(0))/(2))=-x((T_(0))/(2))=-(T_(0))/(2)],[:.x(T_(0))=-(T_(0))/(2)]:}at t=(T_(0))/(2){:[t=-(T_(0))/(2)quad x(t+ ... See the full answer